New Testament essentials : father, son, spirit, and kingdom - Castleman, Robbie, 1949- (InterVarsity Press, 2014)
""I was introduced to the gospel of Jesus Christ as a college student. The Jesus of the New Testament overwhelmed me, and by God's grace Jesus still does, "" writes professor Robbie Castleman, author of New Testament Essentials. Her love of Jesus and Scripture is evident in this study, which seeks to answer the question Jesus' disciples posed: ""What kind of man is this?"" (Matthew 8:27). New Testament Essentials introduces us to the New Testament in three parts: The revelation of God in Jesus Christ, the indwelling of God in the church by the Holy Spirit and the present and.